Proximal renal tubular acidosis with primary Fanconi syndrome - Philip, Prijo; Jacob, Chinthu Sara (International Journal of Contemporary Pediatrics, 2018)
Renal tubular acidosis (RTA) is associated with normal or near normal glomerular filtration rate. Proximal RTA is associated with impaired bicarbonate reabsorption. This is manifested as bicarbonate wastage in the urine, and this reflects the defect in proximal tubular transport. Osteopenia or full-blown rickets may develop. Type 2 RTA is rare and occurs in association with conditions such as Fanconi syndrome. This is manifested as glycosuria, aminoaciduria, phosphate wasting and mild proteinuria. The basis of therapy is the continuous administration of appropriate amounts of alkali in the form of either bicarbonate or citrate, as well as the treatment of the cause.